Using quantitative data on postural activity to develop methods to predict and prevent cybersickness - Bailey, George S.; Arruda, Danilo G.; Stoffregen, Thomas A. (Frontiers in Virtual Reality, 2022)
In this article, we discuss general approaches to the design of interventions that are intended to overcome the problem of cybersickness among users of head-mounted display (HMD) systems. We note that existing approaches have had limited success, and we suggest that this may be due, in part, to the traditional focus on the design of HMD hardware and content. As an alternative, we argue that cybersickness may have its origins in the user’s ability (or inability) to stabilize their own bodies during HMD use. We argue that HMD systems often promote unstable postural control, and that existing approaches to cybersickness intervention are not likely to promote improved stability. We argue that successful cybersickness interventions will be designed to promote stability in the control of the body during HMD use. Our approach motivates new types of interventions; we describe several possible directions for the development of such interventions. We conclude with a discussion of new research that will be required to permit our approach to lead to interventions that can be implemented by HMD designers.